Vitamin D insufficiency increases risk of chronic pain among African Americans experiencing motor vehicle collision. Issue 2 (February 2020) - Mauck, Matthew C.; Linnstaedt, Sarah D.; Bortsov, Andrey; Kurz, Michael; Hendry, Phyllis L.; Lewandowski, Christopher; Velilla, Marc-Anthony; Datner, Elizabeth; Pearson, Claire; Domeier, Robert; Fillingim, Roger B.; Beaudoin, Francesca L.; et al.
Abstract : Abstract: African Americans experience an increased burden of motor vehicle collision (MVC), post-MVC musculoskeletal pain, and vitamin D insufficiency. In this prospective multicenter study, we tested the hypothesis that African Americans (n = 133) presenting to the emergency department after MVC with low peritraumatic vitamin D levels would have worse chronic musculoskeletal pain outcomes compared to individuals with sufficient vitamin D. Vitamin D levels were assessed in the early aftermath of MVC through enzyme-linked immunosorbent assay, and pain severity was assessed using the 0 to 10 numeric rating scale at 6 weeks, 6 months, and 1 year. In repeated-measures analysis, African American MVC survivors with vitamin D insufficiency experienced more severe chronic pain (β = 1.18, P = 0.031). In secondary analyses, we assessed for evidence that the effect of vitamin D on post-MVC pain outcomes is mediated, at least in part, by the influence of vitamin D on genetic variants in genes involved in immune system regulation ( IL-10 and NLRP3 ). Genotyping was performed using a genome-wide microarray using collected DNA samples. Secondary analyses suggest that the effect of vitamin D on post-MVC pain outcomes may be influenced by genetic variation in IL-10 and NLRP3 . Further studies are needed to assess the impact of vitamin D insufficiency on pain outcomes in African Americans experiencing MVC and other common trauma exposures, to assess factors affecting this relationship, and to assess the efficacy of administering vitamin D in the immediate aftermath of MVC to prevent chronic pain. Such low-cost, nonopioid interventions are urgently needed to address chronic pain development after MVC. Abstract : Supplemental Digital Content is Available in the Text.African Americans with vitamin D insufficiency at the time of initial emergency evaluation had more severe motor vehicle collision–related musculoskeletal pain during the subsequent year.